Evaluation, complications and treatment of chronic rhinosinusitis - Khatab, Omar Ali; Bajaber, Moataz Ali; Alharbi, Nada Talal; Alharbi, Naif Talal; Alshahrani, Nada Aouda; Fageeh, Nariman Ayman; Salman, Ahmed Zuhair; Omran, Samar Mohammed Al; Alshahrani, Amal Faleh; Mira, Abdulgader Jamal; Marouf, Faris Ayman (International Journal Of Community Medicine And Public Health, 2022)
Chronic rhinosinusitis (CRS) is a disease which commonly affects people of all ages and significantly impacts the quality of life. The clinical symptoms of CRS, which is defined by a chronic inflammation of the sinonasal mucosa, include persistent rhinorrhoea, nasal congestion, sinus pressure, and a diminished sense of smell that lasts longer than 12 weeks. CRS can be categorized into two groups: CRS with nasal polyps and CRS without nasal polyps. Inflammatory, environmental, and host factors are responsible for causing CRS although the mechanism is debatable. Diagnostic examination including anterior rhinoscopy, endoscopy or radiography, ideally from sinus computed tomography, can aid in confirmational diagnosis of CRS. The objective of the treatment is to improve mucociliary clearance, nasal drainage and outflow, reduce local infection and inflammation, and facilitate topical medicament access. Nasal saline irrigation and intranasal corticosteroid sprays are the first-line treatments. Antibiotics may be helpful for patients who have symptoms of a superimposed, acute active sinus infection. Endoscopic sinus surgery may be useful if medical therapy is ineffective. Referrals to otolaryngologists should be made for patients who are not responding to first-line medical therapy. CRS if not treated timely can further lead to complications including development of various diseases such as asthma breathing issues, smell disorders and certain bacterial and fungal infections. Effective treatment of the CRS is hence needed. The purpose of this research is to review the available information about evaluation, complications and treatment of CRS.